2023
DOI: 10.3390/ma17010121
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution in Wear Analysis of Nano-Y2O3 Dispersion Strengthened Ni-Based μm-WC Composite Material Laser Coating

Li Tao,
Yang Yang,
Wenliang Zhu
et al.

Abstract: Oxide-dispersion- and hard-particle-strengthened (ODS) laser-cladded single-layer multi-tracks with a Ni-based alloy composition with 20 wt.% μm-WC particles and 1.2 wt.% nano-Y2O3 addition were produced on ultra-high-strength steel in this study. The investigation of the composite coating designed in this study focused on the reciprocating friction and wear workpiece surface under heavy load conditions. The coating specimens were divided into four groups: (i) Ni-based alloy, nano-Y2O3, and 2 μm-WC (2 μm WC-Y/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies have found that changing the material formula [ 4 , 5 ], laser cladding, and coating reinforced surfaces [ 6 , 7 ] can all improve the wear resistance of cemented carbides. However, the above methods involve many factors such as equipment, technology, cost, and effect, resulting in a certain degree of restrictions on the implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that changing the material formula [ 4 , 5 ], laser cladding, and coating reinforced surfaces [ 6 , 7 ] can all improve the wear resistance of cemented carbides. However, the above methods involve many factors such as equipment, technology, cost, and effect, resulting in a certain degree of restrictions on the implementation.…”
Section: Introductionmentioning
confidence: 99%